Test the Efficiency of Some Plants Scattered in The Northwestern Part of Karbala City in The Deposition of Dust and Uptake of Heavy Metals - Al-hesnawi, Asaad Sh.M.; Alsalman, Ibrahim M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The study was designed in the northwestern part of Karbala city for the purpose of knowing the efficiency of some plant species of trees and shrubs planted by the municipality of the city to contribute to the deposition of dust particles suffered by the city's environment, in particular, as well as its ability to accumulate heavy metals in dust or soil, and to consider the study model for application in different parts of Iraq. It was found that the plant species (Acacia , Eucalyptus , Clkonukiyrs and Dodenia)  in the studied area that were given the symbols (A,B,C and D respectively).  Used the method of calculating the leaf area index to calculate the amount of dust drawn by the stock plant, then chemical digestion dry and wet techniques spectroscope Flame atomic and spectroscope atomic Flame is to detect the level of metals (lead, Pb, cadmium Cd, Selenium, Se, chromium, Cr, cobalt, Co, As, iron Fe, zenc, Zn, and manganese Mn) accumulated in the leaves of each type of plant.        It was recorded in the resent study  four genera of plants ( Acacia , Alkonukiyrs , eucalyptus andDodenia)  and given the symbols A, B, C and D , respectively), the results show the superiority leaves (B) in the deposition of particles of airborne dust where recorded 3168.50 and 1581.86 Mikgm/cm2 paper , followed by leaf (D) 1630, and 1562.06 Mikgm /cm2 and then leaves (C) 1254.82 and 1317.83 Mikgm / cm2 , followed by leaf (A) and recorded 581.25 and 1071.87 Mikgm/cm2 weight dry and wet respectively . As for the accumulation of heavy metals (lead , cadmium , selenium , chromium , cobalt , tin , iron , zinc , and manganese ), the results show that the plant (A ) had the highest capacity in the accumulation of most of the elements studied , followed by the plant (C) and plant (D ) and leaf (B). was the order of items cumulatively in plants follows : Fe > Se > Zn >Mn> Cu> As >Pb> Co > Cd > Cr, as recorded rates respectively ( 95.4 , 58.2 , 32.5 , 31.8 , 10 , 6.2 , 1.72 , 1.67 , 1.43 and 0.32 Mikgm /cm2